cPCN-Regulated SnO2 Composites Enables Perovskite Solar Cell with Efficiency Beyond 23% - Li, Zicheng; Gao, Yifeng; Zhang, Zhihao; Xiong, Qiu; Deng, Longhui; Li, Xiaochun; Zhou, Qin; Fang, Yuanxing; Gao, Peng (Nano-Micro Letters, 2021)
Efficient electron transport layers (ETLs) not only play a crucial role in promoting carrier separation and electron extraction in perovskite solar cells (PSCs) but also significantly affect the process of nucleation and growth of the perovskite layer. Herein, crystalline polymeric carbon nitrides (cPCN) are introduced to regulate the electronic properties of SnO2 nanocrystals, resulting in cPCN-composited SnO2 (SnO2-cPCN) ETLs with enhanced charge transport and perovskite layers with decreased grain boundaries. Firstly, SnO2-cPCN ETLs show three times higher electron mobility than pristine SnO2 while offering better energy level alignment with the perovskite layer. The SnO2-cPCN ETLs with decreased wettability endow the perovskite films with higher crystallinity by retarding the crystallization rate. In the end, the power conversion efficiency (PCE) of planar PSCs can be boosted to 23.17% with negligible hysteresis and a steady-state efficiency output of 21.98%, which is one of the highest PCEs for PSCs with modified SnO2 ETLs. SnO2-cPCN based devices also showed higher stability than pristine SnO2, maintaining 88% of the initial PCE after 2000 h of storage in the ambient environment (with controlled RH of 30% ± 5%) without encapsulation. Highlights: 1 The (SnO2-cPCN) ETL shows superior electron mobility of 3.3 × 10−3 cm2 V−1 s−1, which is about three times higher than that of pristine SnO2. 2 The less wettable SnO2-cPCN leads to perovskite layers with reduced grain boundaries and enhanced qualities due to suppressed heterogeneous nucleation of perovskite. 3 The PSCs based on SnO2-cPCN showed negligible J–V hysteresis and two champion PCE of 23.17% and 20.3% on devices with 0.1 and 1 cm2 active area, respectively.